Interpersonal Communication and Long-Distance Relationships: A Narrative Study on Students of Community Service in Ciledug Kulon Village - Budi Yuliantoro; Evi Satispi; Maya Puspita Dewi (Journal Of Social Science (JoSS), 2026)
Indonesia, as an archipelago, faces logistical challenges in distributing aviation fuel for TNI AU operations, particularly in remote areas with limited infrastructure. The reliance on conventional methods (such as drums) leads to inefficiencies in time and capacity. The objectives of this study are to analyze the potential application of Bulk Aviation Transport Tank (BATT) innovation in supporting TNI AU aircraft fuel distribution, identify supporting and hindering factors, and provide effective recommendations for its implementation. This research uses a descriptive-analytical qualitative method with data collection through document studies, in-depth interviews with key informants from TNI AU and BRIN, and observation. Data were analyzed interactively using triangulation techniques for validation. The results show that BATT has the potential to significantly improve distribution efficiency: reducing distribution time from 3–5 days to less than 24 hours, increasing fuel utilization to 98%–100%, and optimizing airlift capacity. Key supporting factors include operational efficiency and flexibility, while obstacles include high initial investment needs, limited human resources and infrastructure readiness, and the lack of specific SOPs. Recommendations focus on strengthening policies, human resource development, infrastructure modernization, and partnerships with the domestic defense industry.